Reference values for the incremental shuttle walking test - Probst, Vanessa S.; Hernandes, Nidia A.; Teixeira, Denilson C.; Felcar, Josiane M.; Mesquita, Rafael B.; Gonçalves, Cristiane G.; Hayashi, Daniela; Singh, Sally; Pitta, Fabio (Respiratory medicine, 2012)
Reference values for the incremental shuttle walking test (ISWT) which are applicable to the whole population need to be solidly established. This study aimed to determine which anthropometric and demographic variables influence the walking distance achieved in the ISWT in healthy subjects with a broad age range and to establish a reference equation for predicting ISWT for that population. In a cross-sectional study, 242 healthy subjects (102 male) performed two ISWT and had their weight, height and body mass index (BMI) measured. In general, healthy subjects walked 810 [IQR 25–75%: 572–1030] m in the ISWT, presenting large variability (range 210–1820 m). The walked distance correlated with age ( r = −0.76), height ( r = 0.49) and BMI ( r = −0.23) ( p < 0.001 for all), but not with weight ( r = 0.06, p = 0.315). A model of stepwise multiple regression showed that gender, age and BMI were independent contributors to the ISWT in healthy subjects, explaining 71% ( p < 0.0001) of the variability. The derived reference equation was: ISWT pred = 1449.701 −  (11.735 × age) + (241.897 × gender) − (5.686 × BMI), where male gender = 1 and female gender = 0. In conclusion, the variability of the ISWT is explained largely by gender, age and BMI. The reference values for the ISWT can be adequately predicted using the equation proposed in this study.